Monitoring Macan Tutul Jawa (Panthera pardus melas Cuvier, 1809) dengan Kamera Trap di Cagar Alam Nusakambangan Timur Kabupaten Cilacap, Provinsi Jawa Tengah - Budi Santoso; Wahyono Restanto (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2021)
Monitoring of the existence of the Javan Leopard (Panthera pardus melas) in the Nusakambangan Timur Nature Reserve, Cilacap Regency, has been carried out in July-November 2020. Monitoring is carried out using the method of collecting signs of animal presence and installing camera traps. Photos / videos caught on camera traps are counted on the encounter rate. The monitoring results obtained 97 videos which were divided into 6 videos of P.p. melas, 15 videos of wild boar (Sus scrofa), 1 video of mouse deer (Tragulus javanicus), 2 videos of mountain squirrels (Tupaia montana), 1 video of mice (Apodemus sp.) 20 videos of human activities, and 47 videos of non detection. The result of the Encounter Rate calculation shows the result of P.p. melas 4.44 / 100 days; wild boar 11.85 / 100 days; Squirrels 1.48 / 100 days; rats and mouse deer 0.74 / 100 days, respectively. Meanwhile, for the trail of P.p. melas found 2 impurities.